2022
DOI: 10.3171/2021.7.jns211172
|View full text |Cite
|
Sign up to set email alerts
|

Resection of symptomatic non–small cell lung cancer brain metastasis in the setting of multiple brain metastases

Abstract: OBJECTIVE Current guidelines primarily suggest resection of brain metastases (BMs) in patients with limited lesions. With a growing number of highly effective local and systemic treatment options, this view may be challenged. The purpose of this study was to evaluate the role of metastasectomy, disregarding BM count, in a comprehensive treatment setting. METHODS In this monocentric retrospective analysis, the authors included patients who underwent resection for at least 1 BM and collected demographic, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Brain metastasis from lung cancer is the most prevalent intracranial metastatic malignancy [ 24 ]. Brain metastasis is the leading cause of death in lung cancer patients and one of the common causes of treatment failure [ 25 , 26 ], and the patients are often accompanied by neurological dysfunction caused by the occupancy of brain metastases and have inferior quality of life [ 27 , 28 ]. Spinal cord metastasis—also malignant metastasis—is characterized by rapid clinical progression and a poor prognosis [ [29] , [30] , [31] , [32] ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastasis from lung cancer is the most prevalent intracranial metastatic malignancy [ 24 ]. Brain metastasis is the leading cause of death in lung cancer patients and one of the common causes of treatment failure [ 25 , 26 ], and the patients are often accompanied by neurological dysfunction caused by the occupancy of brain metastases and have inferior quality of life [ 27 , 28 ]. Spinal cord metastasis—also malignant metastasis—is characterized by rapid clinical progression and a poor prognosis [ [29] , [30] , [31] , [32] ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified that age, surgical treatment of the primary tumour, KPS, extracerebral metastasis, targeted therapy, NSE level, ALP level, and PLR are factors that influence the prognosis of NSCLC patients with BM ( Rodrigus, de Brouwer & Raaymakers, 2001 ; Sanchez de Cos et al, 2009 ; Fuchs et al, 2021 ; Junger et al, 2021 ; Yu et al, 2021 ; Jacot et al, 2001 ; Cho et al, 2021 ). In our model, five individual prognostic factors, namely NSE, PLR, ALP, intrathoracic metastasis, and targeted therapy, were identified.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,[22][23][24]32,33,[37][38][39][40][41] However, these retrospective cohorts include few or no patients with multiple brain metastases. Additional reports on surgery in patients with multiple brain metastases [42][43][44][45][46][47] are often limited by a lack of nonsurgical comparison groups. Some studies also focus exclusively on a single tumor type or patients treated before advances in targeted therapy and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%